Access to and Use of Nutrition Information Among Pregnant Women in Makete District, Tanzania - Mruma, Fransisca J.; Mkhai, Emmanuel M. (University of Dar es Salaam Library Journal, 2023)
This paper presents the results of a study that was undertaken to investigate pregnant women ' s nutrition information needs and how these women access such information. The study used a descriptive research design to collect and analyse data from 80 pregnant women and 10 nurses from two healthcare facilities namely Makete District hospital and Ipelele Health Centre. Data were collected using a questionnaire survey which was administered to pregnant women. Focus group discussions were conducted to solicit the women ' s views about the topic in question, and interviews were conducted with the healthcare providers to solicit their perception about the women ' s nutrition information needs and how the women access such information. While content analysis was used to analyse qualitative data, descriptive statistics were used to analyse quantitative data with the help of IBM SPSS version 23. Findings from the study revealed that pregnant women had a number of nutrition information needs. These range from the need to be provided with nutrition information that will help them prepare the best diet during and after their pregnancy, to the type of supplementary nutrients to add to their diet, and how to best protect their food from contamination. The findings further show that to meet their different nutrition information needs, the women had to consult a variety of sources including healthcare providers, mass media sources, and their friends. However, of all the sources identified, nurses were the main sources that were utilized by many pregnant women. Despite showing interest in a number of nutrition information, this study ' s findings revealed that some pregnant women failed to make use of that information, thus putting themselves and their unborn babies at risk. The study concludes that nutrition information is vital for the health of pregnant women and their unborn babies. It is thus essential for pregnant women to access and effectively utilize such information to enhance their maternal outcomes.